2021
DOI: 10.1364/boe.441225
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxicity induced in living HeLa cells by focused femtosecond laser pulses: a data-driven approach

Abstract: Nonlinear optical microscopy is a powerful label-free imaging technology, providing biochemical and structural information in living cells and tissues. A possible drawback is photodamage induced by high-power ultrashort laser pulses. Here we present an experimental study on thousands of HeLa cells, to characterize the damage induced by focused femtosecond near-infrared laser pulses as a function of laser power, scanning speed and exposure time, in both wide-field and point-scanning illumination configurations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…[ 55 ] On the other hand, in a systematic photo‐damage study with an irradiance of two orders of magnitude higher than ours, cells were reported to sustain without noticeable damage for 15‐s exposure. [ 56 ] In contrast, the laser‐on time for one 3D RI image was 10 s in our study. This was a very safe value.…”
Section: Resultsmentioning
confidence: 63%
“…[ 55 ] On the other hand, in a systematic photo‐damage study with an irradiance of two orders of magnitude higher than ours, cells were reported to sustain without noticeable damage for 15‐s exposure. [ 56 ] In contrast, the laser‐on time for one 3D RI image was 10 s in our study. This was a very safe value.…”
Section: Resultsmentioning
confidence: 63%
“…Therefore, in practice, strong light irradiation is required to obtain a good signal; however, this causes photodamage to the cell. When cells are exposed to strong light, reactive oxygen species are internally produced, which can destroy DNA, mitochondria, and other organelles, thereby leading to cell death [ 13 ]. Additionally, metabolic activity may change as a result of resistance to light irradiation, which is included as false signals in the acquired Raman scattering spectrum.…”
Section: Raman Observation Of Living Cellsmentioning
confidence: 99%
“…Even when fluorescent blurring and specimen thickness as well as spherical aberration are taken into account, scattering of light by the tissue sample is another factor that must be considered. As part of their defense mechanism against photo‐toxicity, most cells and tissues are translucent, semi‐opaque structures that scatter and diffuse light very effectively (For a recent discussion of photo‐toxicity in multi‐photon microscopy, see Talone et al., 2021). Thus, when imaging tissues of any appreciable thickness, light scattering limits the extent to which the out‐of‐focus background emission signal can be restricted by the confocal pinhole and an in‐focus image can be successfully acquired.…”
Section: Introductionmentioning
confidence: 99%